Moving subjects, moving objects: transnationalism, cultural production and emotions - Svasek, Maruska (Material mediations, 2012)
In recent years an increasing number of scholars have incorporated a focus on emotions in their theories of material culture, transnationalism and globalization, and this book aims to contribute to this field of inquiry. It examines how 'emotions' can be theorized, and serves as a useful analytical tool for understanding the interrelated mobility of humans, objects and images. Ethnographically rich, and theoretically grounded case studies offer new perspectives on the relations between migration, material culture and emotions. While some chapters address the many different ways in which migrants and migrant artists express their emotions through objects and images in transnational contexts, other chapters focus on how particular works of art, everyday objects and artefacts can evoke feelings specific to particular migrant groups and communities. Case studies also analyse how artists, academics and policy makers can stimulate positive interaction between migrants and non-migrant communities.